METODE DAKWAH RASULULLAH SAW DALAM MENYEHATKAN UMMAT - Dewi Mustika (Fakultas Ushuluddin Adab dan Dakwah IAIN Metro-Lampung, 2018)
Islam is a perfect religion and covers all aspects of life. There is no partition between one life and the other aspects of life. Islam also cannot be separated from the aspects of health and medicine in it. Even the Prophet Muhammad SAW taught us a method of treatment sourced directly from the Owner of Healing. It is through the Qur'an and the Sunnah of the Prophet Muhammad that Islam guides people towards a healthy life both physically and mentally based on the concept of divine, scientific and natural medicine. Thibbun Nabawi is not the only system of health that is systematically monolithic as some people want us to believe. This varies according to conditions, including conditions, preventive medicine, curative medicine, good mental state, spiritual well-being, ruqyah, health care alhmah and surgical practices so that tibbun nabawi unites with mind and body, spirit and body. Thus, the tradition of Prophet-style medicine did not stop at the teaching of medicine by the Messenger of Allah, but rather to encourage people to continue searching and experimenting with new medicine, this implies that Prophet-style medicine is not static. There is room for development and even the basis for new knowledge.